2002
DOI: 10.1152/ajpgi.00535.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peptides derived from dietary proteins on mucus secretion in rat jejunum

Abstract: The hypothesis that dietary proteins or their hydrolysates may regulate intestinal mucin discharge was investigated in the isolated vascularly perfused rat jejunum using an enzyme-linked immunosorbent assay for rat intestinal mucins. On luminal administration, casein hydrolysate [0.05-5% (wt/vol)] stimulated mucin secretion in rat jejunum (maximal response at 417% of controls). Lactalbumin hydrolysate (5%) also evoked mucin discharge. In contrast, casein, and a mixture of amino acids was without effect. Chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 42 publications
2
67
2
Order By: Relevance
“…Claustre et al (2002) found that milk protein hydrolysates (casein and lactalbumin hydrolysates) and b-casomorphin-7 induced mucin release in rat jejunum and Han et al (2008) showed that feeding rats with hydrolyzed casein upregulated Muc3 expression in the gut. Growing rats fed with dietary fibers with increasing viscosities were associated with an increase in ileal endogenous nitrogen flow and mucoprotein (sialic acid) secretion (Larsen et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Claustre et al (2002) found that milk protein hydrolysates (casein and lactalbumin hydrolysates) and b-casomorphin-7 induced mucin release in rat jejunum and Han et al (2008) showed that feeding rats with hydrolyzed casein upregulated Muc3 expression in the gut. Growing rats fed with dietary fibers with increasing viscosities were associated with an increase in ileal endogenous nitrogen flow and mucoprotein (sialic acid) secretion (Larsen et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The mucus layer is affected by numerous dietary components and the reported beneficial effects of dietary Ig on gut health may be due, at least in part, to effects -E-mail: p.j.moughan@massey.ac.nz on the mucus layer (Claustre et al, 2002;Dock-Nascimento et al, 2007;Han et al, 2008;King et al, 2008). Recently, we have reported that feeding a freeze-dried ovine serum Ig preparation selectively improves growth performance, the weight of some digestive organs and gut morphology in the growing rat (Balan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a study to determine effects of peptides derived from dietary proteins on mucus secretion, Claustre et al (2002) revealed that two protein hydrolysates obtained by enzymatic hydrolysis of casein and lactalbumin prompted mucin release in rat jejunum. Later, Mart ınez-Maqueda et al (2013a, b) found that two peptides derived from casein hydrolysate induce mucin production in human intestinal cells.…”
Section: Prebiotic Effectsmentioning
confidence: 99%
“…Glycoprotein output was shown to increase at the duodenum (+24%) and ileum (+52%) with potato protein concentrate [21]. In an in vitro model of the rat jejunum, two enzymatically hydrolyzed milk protein sources, namely casein and lactalbumin, induced mucin release in the lumen [7]. Thus, direct or indirect specific interactions could exist between dietary proteins and/or peptides resulting from their hydrolysis and goblet cells for releasing mucin.…”
Section: Ileal Glycoprotein Output and Differences Between Dietsmentioning
confidence: 99%
“…Because this glycoprotein is poorly digested before reaching the large intestine, where it is fermented by enteric bacteria [5], it represents one of the most significant contributions to endogenous protein flowing out of the small intestine [6]. There is now some evidence that intestinal glycoprotein flow is modulated by dietary components including fiber, protein and antinutritional factors [7][8][9]. So, measuring the glycoprotein flow in the gut lumen could provide insights into the effect of the diet or dietary components on gut physiology.…”
Section: Introductionmentioning
confidence: 99%